Pengembangan Sistem Transaksi Penjualan dan Pembelian Pada Peron Sawit Menggunakan Aplikasi - Rizki Novendra; Syahtriatna; M Sadar; Viranda Anisa (Universitas Lancang Kuning, 2019)
Applying information system technology to business processes is one of the strategies to overcome about problems in data accuration, sales, purchases and making report transactions. By implementing the system, information has resulted at decreased in time transaction and accuracy of the sales, purchase and report making processes. The application of information system technology starts in analysis, design, implementation, testing and maintenance according to the waterfall method. Each stage has a different resolution and function, but is interrelated between one and the other generated by computer applications that can be used in the business of the company CV. Saragih 3 Brothers